Transcutaneous Spinal Direct Current Stimulation - Cogiamanian, Filippo; Ardolino, Gianluca; Vergari, Maurizio; Ferrucci, Roberta; Ciocca, Matteo; Scelzo, Emma; Barbieri, Sergio; Priori, Alberto (Frontiers in Psychiatry, 2012)
In the past ten years renewed interest has centered on non-invasive transcutaneous weak direct currents applied over the scalp to modulate cortical excitability (“brain polarization” or transcranial direct current stimulation, tDCS). Extensive literature shows that tDCS induces marked changes in cortical excitability that outlast stimulation. Aiming at developing a new, non invasive, approach to spinal cord neuromodulation we assessed the after-effects of thoracic transcutaneous spinal DC stimulation (tsDCS) on somatosensory potentials (SEPs) evoked in healthy subjects by posterior tibial nerve (PTN) stimulation. Our findings showed that thoracic anodal tsDCS depresses the cervico-medullary PTN-SEP component (P30) without eliciting adverse effects. tsDCS also modulates post-activation H-reflex dynamics. Later works further confirmed that transcutaneous electric fields modulate spinal cord function. Subsequent studies in our laboratory showed that tsDCS modulates the flexion reflex in the human lower limb. Besides influencing the laser evoked potentials, tsDCS increases pain tolerance in healthy subjects. Hence, though the underlying mechanisms remain speculative, tsDCS modulates activity in lemniscal, spinothalamic and segmental motor systems. Here we review currently available experimental evidence that non-invasive spinal cord stimulation influences spinal function in humans and argue that, by focally modulating spinal excitability, tsDCS could provide a novel therapeutic tool complementary to drugs and invasive spinal cord stimulation in managing various pathologic conditions, including pain.